Reinforcing in the Production of Gypsum Materials on Base Wollastonite Fibers - Mamatqosim, Bekkamov; Aziza, Kuldasheva (European Journal of Life Safety and Stability (2660-9630), 2021)
laThere are given properties of testing in nano-lab-testing and using it in gypsum materials nowadays. The addition of wollastonite to the gypsum is carried out as follows: it is poured into the dry consist and mixed. Thus, the addition of wollastonite reduces shrinkage deformations and improves the technological properties of dry mixes